Average-cost Pricing and Dynamic Selection Incentives in the Hospital Sector - Mathias Kifmann; Luigi Siciliani (Center for Economic Studies and ifo Institute (CESifo), 2014)
This study investigates hospitals' dynamic incentives to select patients when hospitals are remunerated according to a prospective payment system of the DRG type. Given that prices typically reflect past average costs, we use a discrete-time dynamic framework. Patients differ in severity within a DRG. Providers are to some extent altruistic. For low altruism, a downward spiral of prices is possible which induces hospitals to focus on low-severity cases. For high altruism, dynamic price adjustment depends on relation between patients' severity and benefit. In a steady state, DRG prices are unlikely to give optimal incentives to treat patients.
Keywords: I11; I18; L13; L44; 330; hospitals; DRGs; selection; severity